Analysis Of Leadership, Compensation and Its Influence on Work Motivation and Implications on Teacher Performance - Suarni Norawati; Syafarisna Syafarisna (eCo-Buss, 2023)
Teachers play an important role in the world of education, both formal, non-formal and informal education. In carrying out their duties as teachers, high work motivation is needed so that teacher performance can be improved, so that the quality of graduates can be realized. To realize this, it is necessary to have the right leadership of the principal and provide compensation in accordance with the wishes of the teacher, so that what was the goal of the previous school can be realized. This research was conducted at SMPN 1 Kubu Rokan Hilir Regency with the aim of the study, namely to determine and analyze the influence of leadership, leadership and compensation on teacher performance both directly and indirectly. The population of this study is 60 teachers, all of whom are sampled, so the census method is used for sampling. Structural Equation Modeling (SEM) was used to perform the data analysis tool model, and data processing was performed using SmartPLS software version 3.0. The findings indicate that leadership and compensation have a significant direct impact on teacher performance. Leadership has a significant impact on teacher performance through teachers' work motivation. This means that the better the headteacher's leadership in managing and managing all resources, the more motivated teachers are to get things done, and therefore teacher performance, and vice versa. Compensation has a major impact on teacher performance through job incentives of SMPN 1 Kubu teachers, Rokan Hilir Regency. This means that the amount of compensation received by each teacher will determine whether or not the teacher's work motivation is good, this has an impact on the level of achievement of teacher performance in carrying out their duties at school.